Pengaruh Lama Pendiaman Santan, Cara Penyaringan dan Lama Penyimpanan Terhadap Mutu Virgin Coconut Oil (VCO) - RINDENGAN BARLINA (Buletin Palma, 2009)
Influence of Fermentation, Filtering and Storage Time on Quality ofVirgin Coconut Oil (VCO)Virgin Coconut Oil (VCO), is a product of the processing without the addition of food additive, that is categorized as natural products. Since 2003, the product is known of consumer because it is very beneficial for health, so its expensive, so many emerging ways of processing. Therefore, in 2004, has conducted research to find practical ways for the farmers, including fermentation of coconut milk (3 hours and 12 hours), filtering (using filter paper 42 mess, straining cloth and only muted 3 days ), then VCO observed at 0-month storage, 2 months, 4 months and 6 months. Observations carried out on the water content, free fatty acid and peroxide numbers. The results showed that water levels are influenced by long storage and interaction of fermentation coconut milk, filtering and storage. Free fatty acids is not affected by any treatment, while the peroxidevalue affected by long storage. VCO water content of 0-6 months of storage ranged 0.07-0.13%, free fatty acids ranging from 0.17-0.23% and the peroxide value ranges from 0.19-3.02 meq/kg oil. The range of water content, free fatty acid and peroxide value, still meet the standards of Asian Pasific Coconut Community (APCC), the water content ranges from 0.1-0.5%, maximum free fatty acids 0.5% and a maximum peroxide number 3 meq /kg. Based on the results of this study, the VCO processing by applying the processing is done, continue to produce VCO that meet the standards set APCC.